The Influence of Innovation Strategy on Sustainable Competitive Advantage - Try Ayu Nuragita; Siti Nursyamsiah (PT Mattawang Mediatama Solution, 2024)
This study examines the influence of innovation strategy on sustainable competitive advantage through a functional innovation approach, innovation process, and innovation system. This research utilized survey data conducted on MSMEs in Yogyakarta with a total sample of 95 respondents. In order to answer the research hypothesis, this study employed the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis tool using SmartPLS tools. The results of the study indicate that there is an influence of innovation strategy on the innovation process and system, as well as the influence of the innovation process and system on sustainable competitive advantage. This research has contributed to the development of innovation strategies in building sustainable competitive advantage in MSMEs.